Ativismos e a cidade: redes de resistência na produção do urbano - Laís Grossi de Oliveira (2016)
The universe of this research consists of 39 urban activisms from Belo Horizonte, Brazil, understood as civil society groups that counteract the dominant spatial dynamics. We seek to understand their constitution as collective actors in the production of urban space, especially in moments when it is possible to articulate groups, through which their political representation is enlarged. For such, the research relies on the analysis of interviews with activists, on the literature produced on the subject and on monitoring the actions of activisms fanpages on facebook, between September 2015 and May 2016. The city, as a product and producer of the relations of domination that are established in our society, could not have another configuration than an unequal, fragmented and segregated one. Seeking to break this dynamic, the activisms that delimit a universe of wide approaches, tactics, political positions and claim issues emerge as a force in the dispute over the production of urban space, with or (more commonly) against the State and the private initiative. It is evident the asymmetry of power in this context, mainly when we consider that, frequently, activisms are in opposition to the other actors. A raise of expressivity and, therefore, political power is achieved when articulations surrounding common struggles are undertaken. However, shaped in moments of emergency when losses are expected, they configure, above all, networks of resistance.